2021
DOI: 10.1093/plcell/koab044
|View full text |Cite
|
Sign up to set email alerts
|

Function of the HYDROXYCINNAMOYL-CoA:SHIKIMATE HYDROXYCINNAMOYL TRANSFERASE is evolutionarily conserved in embryophytes

Abstract: The plant phenylpropanoid pathway generates a major class of specialized metabolites and precursors of essential extracellular polymers that initially appeared upon plant terrestrialization. Despite its evolutionary significance, little is known about the complexity and function of this major metabolic pathway in extant bryophytes, which represent the non-vascular stage of embryophyte evolution. Here, we report that the HYDROXYCINNAMOYL-CoA:SHIKIMATE HYDROXYCINNAMOYL TRANSFERASE (HCT) gene, which plays a criti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
75
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(94 citation statements)
references
References 88 publications
4
75
0
Order By: Relevance
“…Overall, the topology of the tree corroborates the findings of Kriegshauser et al. (2021) that a clear clade of HCT proteins first emerged in land plants—streptophyte algal sequences were few, divergent from HCT, and scattered over the tree without clear affinity to characterized acyltransferases. Without functional analyses, there is no solid foundation for predicting their function—making them exciting candidates for future studies.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Overall, the topology of the tree corroborates the findings of Kriegshauser et al. (2021) that a clear clade of HCT proteins first emerged in land plants—streptophyte algal sequences were few, divergent from HCT, and scattered over the tree without clear affinity to characterized acyltransferases. Without functional analyses, there is no solid foundation for predicting their function—making them exciting candidates for future studies.…”
Section: Resultssupporting
confidence: 85%
“…Recently, Kriegshauser et al. (2021) reported on the functional conservation of the HCT homologs found in bryophytes with those of seed plants.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, already in early land plants, the canonical CYP98 has been required for plant aerial growth and for the formation of essential biopolymers. Early on, it used the p-coumaroyl shikimate ester as a main substrate for phenolic ring meta-hydroxylation forming a regulatory shikimate-sensing loop for the biochemical regulation of the lignin pathway (Kriegshauser et al, 2021).…”
Section: Cyp98mentioning
confidence: 99%
“…The orthologs of HCTs are present among all the land plants, which suggests that this enzyme evolved before the occurrence of lignin. A recent study showed that P. patens HCT and Marchantia polymorpha HCT can complement the deficiency of Arabidopsis hct mutant in terms of morphology and metabolite levels, suggesting that the function of HCT is likely conserved in all embryophytes (Kriegshauser et al, 2021). It appears that gene duplication of HCT occurred in dicots that produced the HQT gene.…”
Section: G-and S-lignin Biosynthesis In Angiospermsmentioning
confidence: 99%
“…Lignins appeared as specialized metabolites with the evolution of tracheophytes. The identification of progenitors of lignin biosynthetic genes in bryophytes provides new insights into the origin of lignin biosynthesis (Kriegshauser et al, 2021). The recent progress on genome sequencing of Charophyte algae, bryophytes, lycophytes, and ferns have also provided unprecedented opportunities to study the origin of phenylpropanoid biosynthetic pathway (Szövényi et al, 2021).…”
Section: Perspectives On the Origin And Evolution Of Lignin Biosynthesis In Plantsmentioning
confidence: 99%